Withdrawal of ventilation at the patient's request in MND: a retrospective exploration of the ethical and legal issues that have arisen for doctors in the UK. Issue 2 (11th September 2015) - Phelps, Kay; Regen, Emma; Oliver, David; McDermott, Chris; Faull, Christina
Abstract : Background: Ventilatory support has benefits including prolonging survival for respiratory failure in motor neurone disease (MND). At some point some patients may wish to stop the intervention. The National Institute of Health and Care Excellence (NICE) guidance recommends research is needed on ventilation withdrawal. There is little literature focusing on the issues doctors encounter when withdrawing ventilation at the request of a patient. Aim: To identify and explore with doctors the ethical and legal issues that they had encountered in the withdrawal of ventilation at the request of a patient with MND. Method: A retrospective thematic analysis of interviews of 24 doctors (including palliative care, respiratory, neurology and general practice) regarding their experiences with withdrawal of ventilation support from patients with MND. Results: Respondents found withdrawal of ventilation at the request of patients with MND to pose legal, ethical and moral challenges in five themes: ethical and legal rights to withdrawal from treatment; discussions with family; discussions with colleagues; experiences of legal advice; issues contributing to ethical complexity. Though clear about the legality of withdrawal of treatment in theory, the practice led to ethical and moral uncertainty and mixed feelings. Many respondents had experienced negative reactions from other healthcare professionals when these colleagues were unclear of the distinction between palliation of symptoms, withdrawal of treatment and assisted death. Conclusions: Legal, ethical and practical guidance is needed for professionals who support a patient with MND who wishes to withdraw from ventilation. Open discussion of the ethical challenges is needed as well as education and support for professionals.